Kepala Penghulu: Kiprah dan Pemikiran R.H. Achmad Djoewaeni Tahun 1912-1940 - Aulia Kusnadi, Yuni (Historia Madania: Jurnal Ilmu Sejarah, 2020)
The leader in the colonial era played an important role in socio-religious sphere. This study discusses the role of R.H. Achmad Djoewaeni as a chief of penghulu, a religious headman in Sukabumi. in carrying out his duties as head of Penghulu, he apparently faced many problems, such as having a different opinion from other religious figures because the leader was considered an extension of the Dutch intervention. This study aims at determining the role of the penghulu in the colonial period, the life history of RH. Achmad Djoewaeni as well as the role of R.H. Achmad Djoewaeni as a head of penghulu in Sukabumi in 1912-1940. The method used in this research is the historical research conducted in four stages, namely heuristics, criticism, interpretation, and historiography. Based on the research, it is concluded that: firstly, R.H. Achmad Djoewaeni served as the leader from 11 November 1912 until his death in 1940. Secondly, the role of R.H. Achmad Djoewaeni as the head of penghulu in Sukabumi is establishing the first formal Islamic school in Sukabumi is, in the field of education, regulating the administration of the Kauman Mosque in the field of religious development, and managing zakat, slametan and transliterating of the holy Quran into Latin letters in the field of thought. Â Keyword : Ulama, penghulu, Colonial policy